Actinomyces lesions and acute inflammation predominate in osteonecrosis of the jaw associated with osteoclast-suppressing therapy in contrast to non-medication-related osteonecrosis - Kivelä-Rajamäki, Marjo; Välimaa, Hanna; Furuholm, Jussi; Haglund, Caj; Sorsa, Timo; Hagström, Jaana; Järvinen, Asko (Springer Nature, 2026)
Purpose
Patients receiving antiresorptive therapy for cancer bone metastases/lesions or osteoporosis may develop osteonecrosis of the jaw. The pathogenesis remains unclear, but the condition has been associated with Actinomyces, co-pathogens, and pro-inflammatory activity. However, there are limited studies comparing these factors between medication-related osteonecrosis and non-medication-related osteonecrosis.
Methods
This is a single-centre retrospective study of 98 patients with jawbone biopsies due to medication-related osteonecrosis treated with bisphosphonates and/or denosumab, and 93 patients with non-medication-related osteonecrosis during 2002–2020. We reviewed their medical records and analysed tissue samples for Actinomyces colonies, inflammation and proinflammatory collagenase matrix metalloproteinase-8 (MMP-8) using immunohistochemistry.
Results
Actinomyces colonies were more prevalent in medication-related osteonecrosis (85%) compared to non-medication-related cases (51%; p < 0.001) and were mainly associated with necrotic bone. Inflammation was present in most samples; however, in medication-related osteonecrosis, it was predominantly acute (58%) and rarely chronic (5%), whereas in non-medication-related biopsies, inflammation was acute in 38% and chronic in 27% of biopsies (p < 0.001). Enhanced MMP-8 immunoreactivity was observed in 61% of medication-related osteonecrosis vs. 38% in non-medication-related biopsies (p = 0.002), and MMP-8 was especially expressed alongside actinomycotic lesions (57% vs. 34%; p < 0.001). In multivariable logistic regression, the medication-related group was independently associated with a higher prevalence of Actinomyces colonies.
Conclusion
Medication-related osteonecrosis was independently linked to a higher prevalence of Actinomyces compared to non-medication-related osteonecrosis. Furthermore, acute inflammation and collagenase activity seemed to be effects of Actinomyces-associated infection. The presence of Actinomyces may suggest immunological differences between these osteonecrosis types.